Improving productivity of the Food and Beverage (F&B) industry using Apple i-Beacon - Teo, Everline (2018)
Estimote iBeacons are small wireless sensors that can be place anywhere to provide information and even micro-locations to smartphone, tablets and other devices. It is a protocol developed by Apple and is a class of Bluetooth low energy (BLE) devices that broadcast their universally unique identifier (UUID) to nearby portable electronic devices. BLE is the basic communication technology in beacons that requires considerably low power consumption to transmit data over short distances.